Book Review: The River Imp and the Stinky Jewel and Other Tales: Monster Comics from Edo Japan - J.T. Aris (Journal of Anime and Manga Studies, 2023)
Review of The River Imp and the Stinky Jewel and Other Tales: Monster Comics from Edo Japan translated by Adam Kabat.